Anatomy and phylogenetic relationships of Temnodontosaurus zetlandicus (Reptilia: Ichthyosauria). Issue 1 (18th February 2022) - Laboury, Antoine; Bennion, Rebecca F; Thuy, Ben; Weis, Robert; Fischer, Valentin
Abstract: Parvipelvia is a major clade of ichthyosaurians that diversified during the Triassic-Jurassic transition. The interrelationships of early parvipelvians remain unclear and many genera are loosely diagnosed, such as Temnodontosaurus, an ecologically important genus from the Early Jurassic of Western Europe. One taxon concentrates many taxonomic issues: ' Ichthyosaurus ' acutirostris was previously assigned to Temnodontosaurus and for which ' Ichthyosaurus ' zetlandicus represents a junior synonym. We redescribe the holotype of ' Ichthyosaurus ' zetlandicus (CAMSM J35176) and a new specimen probably attributable to this taxon (MNHNL TU885) from the Toarcian of Luxembourg. We find that Temnodontosaurus zetlandicus comb. nov. is a valid species that should be referred to the genus Temnodontosaurus, sharing a number of traits with Temnodontosaurus nuertingensis and Temnodontosaurus trigonodon, despite having a distinct cranial architecture. Our phylogenetic analyses under both implied weighting maximum parsimony and Bayesian inference recover T. zetlandicus as closely related to several species currently assigned to Temnodontosaurus . Species included in Temnodontosaurus form a polyphyletic yet well-clustered group among basal neoichthyosaurians, demonstrating that the monophyly of this genus needs to be thoroughly investigated.